"He wants to get rid of all the Muslims": Mexican American and Muslim students' use of history regarding candidate Trump. (2nd July 2020) - Yoder, Paul J.
ABSTRACT: This study employs a multiple case study approach to examine the use of history of Mexican American and Muslim middle school students vis-à-vis Donald Trump's 2016 presidential campaign. The findings suggest the participants used historical examples of discrimination to contextualize candidate Trump's rhetoric and to bolster their identities as both immigrants and Americans. Their cases provide important evidence of the ways in which marginalized youth can use history as a source of resilience and resistance. The findings add to the literature on use of history as an analytic and pedagogical tool and suggest that social studies educators are uniquely positioned to support students through confronting political trauma.